Relationship between motor performance and physical fitness score in 7- to 8-year-old children - Ruy Jornada Krebs; Marcelo Gonçalves Duarte; Glauber Carvalho Nobre; Patrik Felipe Nazario; João Otacilio Libardoni dos Santos (Universidade Federal de Santa Catarina, 2011)
There are many tests for the evaluation of motor performance or physical fitness that take into account different criteria such as movement forms and patterns, time, distance, and repetitions of each task for the analysis of performance. The aim of this study was to investigate the relationship between motor performance and physical fitness scores in children. Fifty children of both genders aged 7 to 8 years (25 boys and 25 girls) participated in this study. The Test of Gross Motor Development - Second Edition (TGMD-2) was used for the evaluation of motor performance. Physical fitness was assessed by three specific tests proposed by the American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD). The results showed statistical significance and weak correlations among some skills such as run, horizontal jump, hop, leap, underhand roll, and medicine ball throw. The equivalent use of both tests may not be adequate since each test has its own peculiarities in terms of assessment criteria.